Experimental Analysis of Optimum Tilt Angle for Higher Efficiency in the Photovoltaic Module - Dr. K G Srinivas; Lakshminarayana T H; Nesanuri Rupesh; Prajwal N; Kiran K; Kishor Naik R (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
This paper determines the most suitable tilt angles for photovoltaic (PV) panels to generate electricity from solar energy. Literature reviews typically focus on maximizing radiation values on fixed panels. However, this study identifies the optimal position for maximizing the total radiation falling on PV panels with varying tilt angles. An experimental setup is established to measure solar radiation, power, and temperature data. The electrical energy, open-circuit voltage, and short-circuit current produced by the PV panels are measured and recorded simultaneously. The performance of PV panels at different tilts on power output is examined and compared. Experimental results have indicated that panel tilt angles significantly impact power generation, currents, and fill factor. This article could serve as a suitable guide for finding the optimal tilt angle for similar locations in the future.
Keywords: Optimal Tilt Angles; Photovoltaic (PV) Panels; Solar Energy Generation; Power Output Performance; Experimental Analysis